2011
DOI: 10.1247/csf.11009
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Roles of .ALPHA.-Catenin in Cell Adhesion and Cytoskeleton Organization: Isolation of F9 Cells Completely Lacking Cadherin-catenin Complex

Abstract: ABSTRACT. To define the roles of α-catenin in cell-cell adhesion, the E-cadherin, α-catenin, β-catenin, and/or plakoglobin genes were inactivated in F9 teratocarcinoma cells. An E-cadherin-α-catenin fusion protein (Eα) restored full cell-adhesion function and organized the actin-based cytoskeleton and ZO-1, an actin filament binding protein, in F9 cells lacking all endogenous cadherin-catenin complex components. There were two types of cadherin-based cell-adhesion junctions in parental F9 cells, those with ZO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…S6G). This strategy has been used previously to constitutively link E-cadherin to the actin cytoskeleton (35,71). However, even such direct engagement of E-cadherin with the .…”
Section: Or 1 Mole % Acyl Chain Labeled 1-acyl-2-[12-[(7-nitro-2-13-mentioning
confidence: 99%
“…S6G). This strategy has been used previously to constitutively link E-cadherin to the actin cytoskeleton (35,71). However, even such direct engagement of E-cadherin with the .…”
Section: Or 1 Mole % Acyl Chain Labeled 1-acyl-2-[12-[(7-nitro-2-13-mentioning
confidence: 99%
“…α-E catenin (Catenin α-1 [CTNNA1]) and β-catenin (Catenin β-1 [CTNNB1]) are markers linking adherens junctions with the actin cytoskeleton [ 54 , 55 ]. Analysis of α-E catenin and β-catenin mRNA expression in hiPSCs (201B7 cell line) showed that expression of α-E catenin mRNA was significantly increased when iMatrix-221 was used as the coating material compared with iMatrix-511 (mean [standard deviation]: iMatrix-511, 1.00 [0.08]; iMatrix-221, 1.30 [0.15]; P = 6.1E-03; n = 6) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies used E-cadΔ70/α and a full-length chimera containing the entire cytoplasmic tail of E-cadherin (E-cad/α) to induce cell–cell adhesion in a variety of cell types and tissues in vitro and in vivo ( Ozawa, 1998 ; Ozawa and Kemler, 1998 ; Imamura et al, 1999 ; Gottardi et al, 2001 ; Winter et al, 2003 ; Pacquelet and Rørth, 2005 ; Qin et al, 2005 ; Abe and Takeichi, 2008 ; Noda et al, 2010 ; Ozono et al, 2011 ; Schulte et al, 2011 ; Maiden and Hardin, 2011 ; Sarpal et al, 2012 ; Shih and Yamada, 2012 ; Twiss et al, 2012 ; Thomas et al, 2013 ; Desai et al, 2013 ; Küppers et al, 2013 ; Dartsch et al, 2014 ). The consensus conclusions from these experiments are that membrane-tethered, monomeric αE-catenin is sufficient for intercellular adhesion by linking the CCC to the actin cytoskeleton, and that neither a cytoplasmic pool of αE-catenin nor αE-catenin homodimers are required ( Ozono et al, 2011 ; Sarpal et al, 2012 ; Desai et al, 2013 ; Thomas et al, 2013 ). However, these interpretations overlook the fact that (a) αE-catenin bound to β-catenin in the CCC has a distinct conformation and different properties compared with free monomeric αE-catenin, and (b) the possibility that the E-cadΔ70/α chimera homodimerizes, a property of mammalian αE-catenin that normally occurs in the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…In fibroblast L cells, which lack endogenous E-cadherin, expression of E-cadΔ70/α induced cell-cell adhesion, which required the C-terminal actin-binding domain (ABD) of αE-catenin (Nagafuchi et al, 1994). Subsequent studies used E-cadΔ70/α and a full-length chimera containing the entire cytoplasmic tail of E-cadherin (E-cad/α) to induce cell-cell adhesion in a variety of cell types and tissues in vitro and in vivo (Ozawa, 1998;Ozawa and Kemler, 1998;Imamura et al, 1999;Gottardi et al, 2001;Winter et al, 2003;Pacquelet and Rørth, 2005;Qin et al, 2005;Abe and Takeichi, 2008;Noda et al, 2010;Ozono et al, 2011;Schulte et al, 2011;Maiden and Hardin, 2011;Sarpal et al, 2012;Shih and Yamada, 2012;Twiss et al, 2012;Thomas et al, 2013;Desai et al, 2013;Küppers et al, 2013;Dartsch et al, 2014). The consensus conclusions from these experiments are that membrane-tethered, monomeric αE-catenin is sufficient for intercellular adhesion by linking the CCC to the actin cytoskeleton, and that neither a cytoplasmic pool of αE-catenin nor αE-catenin homodimers are required (Ozono et al, 2011;Sarpal et al, 2012;Desai et al, 2013;Thomas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%